Respon Pertumbuhan StumpKaret(Hevea brassiliensis Muell Arg.)Terhadap Pemberian Zat Pengatur Tumbuh Dengan Cara Pengolesan Di Luka Pemotongan Akar Tunggang Pada Beberapa Komposisi Media Tanam - Y HERNAWATI P; CHARLOQ ROSA NABABAN; TOGA SIMANUNGKALIT (Universitas Sumatera Utara, 2017)
One of the problems encountered in rubber cultivation with stump is the high percentage of stump death in field caused by the inhibition of roots and shoots growth. So that to accelerate the growth of rooting can be applied by growth regulator. The aim of the research was to found out the response of stump rubber (Hevea brassiliensis Muell Arg.) used of growth regulator in varieth of planting media. The research was conducted in September 2015 until February 2016 of Agriculture Faculty experimental field, Sumatera Utara University, Medan. The research used the completely randomized design with two factors and three replications. The first factor was concentration of growth regulator, i.e : yaitu 0 mg / 2mL water per stum, 25 mg / 2mL water per stum, 50 mg / 2mL water per stum, dan 75 mg / 2mL water per stum mg and the second factor was the plant media comparison of top soil and sand, i.e : 1:0, 1:1, 1:2, 1:3.The results showed the concentration of growth regulator, the plant media top soil : sand (1:1) and their interaction had no significant increased the growth.of.rubber.stump. Keywords: Growth regulator, Plant media, Stump